Arabic Learning Based on Canva Multimedia - Baharun, Segaf; Maliki, Mu'azam (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2023)
This section is separate Changes in the culture of learning foreign languages, especially Arabic, as a result of the use of technology are very dependent on various components in the learning support system. This research can be categorized as a library research. The approach applied in this research is a qualitative approach, which emphasizes the analysis of processes and dynamics of relationships between observed phenomena using scientific logic. Learning videos using Canva are suitable for Arabic language subjects, especially material that requires in-depth understanding. Learning videos through Canva make it possible to create animated images of moving objects so that they look like they can be felt in real life, even though they are semi-concrete.